THE POLITICAL PERSONALITY OF STEPAN BANDERA AND THE RUSSIAN-UKRAINIAN CONFLICT - Mijatović, Marko (Politeia, 2025)
The beginning of a 'special military operation' of the Russian Federation has significantly changed the current political scene of the world and opened up numerous questions, among others, the future of relations between Ukraine and the Russian Federation and between the Russian and Ukrainian people. The strained Russian-Ukrainian relations have been going on for years, and they culminated in the 'Euromaidan' in 2014, when the pro-Western government came to power for the second time after 2004, gaining support of mass protests in the streets of Kyiv, with this political option being still in power today.. In this paper, we deal, given the aforementioned context, with the controversial political figure of Stepan Bandera and his deeds,  as well as his impact on current events in the country, since he has for years now been perceived by both Ukrainians and Russians as a figure-myth of the Ukrainian extreme nationalism.
Keywords: Stepan Bandera; Ukraine; Ukrainians; ukrainian-russian relations; ukrainian-russian conflict